2008
DOI: 10.1007/s10843-008-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Organising new business in a turbulent context: Opportunity discovery and effectuation for IJV development in transition markets

Abstract: Opportunity discovery, Entrepreneurial behaviour, International joint venture, Process,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 51 publications
0
48
0
Order By: Relevance
“…The final theme for Type A entrepreneurship research shows a continuous and creative process in which entrepreneurial managers are absorbed into the emerging social community of the international venture (Mainela and Puhakka, 2009). Opportunity recognition is linked to the personal initiatives of the managers, i.e.…”
Section: Entrepreneurship (Emerged 1997)mentioning
confidence: 99%
“…The final theme for Type A entrepreneurship research shows a continuous and creative process in which entrepreneurial managers are absorbed into the emerging social community of the international venture (Mainela and Puhakka, 2009). Opportunity recognition is linked to the personal initiatives of the managers, i.e.…”
Section: Entrepreneurship (Emerged 1997)mentioning
confidence: 99%
“…In other words, a hostile environment in particular calls for the development of networks (Chakravarthy 1997). Furthermore, turbulent foreign environments specifically call for proactive networking and the use of relationships (Mainela and Puhakka 2009) in order to absorb the high-entry risks (Li and Qian 2008). Welch and Welch (2004) found that the structure of the networks of internationalized firms vary depending on environmental characteristics such as the industry structure and governmental involvement.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…Furthermore, we build on previous research that has initiated the process of integrating effectuation and internationalization process (see Mainela and Puhakka, 2009;Sarasvathy et al 2014;Schweizer et al, 2010). Both effectuation approach and Uppsala model have relationships as a central focus to provide knowledge and opportunity (Johanson and Vahlne, 2009;Sarasvathy, 2001).…”
Section: Introductionmentioning
confidence: 99%